Locus specific endogenous retroviral expression associated with Alzheimer’s disease - Dawson, Tyson; Rentia, Uzma; Sanford, Jessie; Cruchaga, Carlos; Kauwe, John S. K.; Crandall, Keith A. (Frontiers in Aging Neuroscience, 2023)
INTRODUCTION: Human endogenous retroviruses (HERVs) are transcriptionally-active remnants of ancient retroviral infections that may play a role in Alzheimer's disease.METHODS: We combined two, publicly available RNA-Seq datasets with a third, novel dataset for a total cohort of 103 patients with Alzheimer's disease and 45 healthy controls. We use Telescope to perform HERV quantification for these samples and simultaneously perform gene expression analysis. 2 RESULTS: We identify differentially expressed genes and differentially expressed HERVs in Alzheimer's disease patients. Differentially expressed HERVs are scattered throughout the genome; many of them are members of the HERV-K superfamily. A number of HERVs are correlated with the expression of dysregulated genes in Alzheimers and are physically proximal to genes which drive disease pathways. DISCUSSION: Dysregulated expression of ancient retroviral insertions in the human genome are present in Alzheimer's disease and show localization patterns that may explain how these elements drive pathogenic gene expression.